2020
DOI: 10.1002/advs.202002643
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Imaging of Cholesterol Assemblies Reveals Hidden Nanomechanics of Breast Cancer Cells

Abstract: Tumor cells present profound alterations in their composition, structural organization, and functional properties. A landmark of cancer cells is an overall altered mechanical phenotype, which so far are linked to changes in their cytoskeletal regulation and organization. Evidence exists that the plasma membrane (PM) of cancer cells also shows drastic changes in its composition and organization. However, biomechanical characterization of PM remains limited mainly due to the difficulties encountered to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 67 publications
(71 reference statements)
3
39
0
Order By: Relevance
“…This model includes three human mammary cell lines, which offer the same background but increasing degrees of malignancy: MCF10A (A, non-tumorigenic), MCF10AT (AT, pre-malignant) and MCF10CAIa (CAIa, malignant) [ 24 ]. We showed that, while the cytoskeleton of the malignant CAIa cell line is, as expected, softer than normal A cells, its PM is surprisingly stiffer and correlates with higher surface chol content and cell malignancy [ 23 ].…”
Section: Introductionmentioning
confidence: 82%
“…This model includes three human mammary cell lines, which offer the same background but increasing degrees of malignancy: MCF10A (A, non-tumorigenic), MCF10AT (AT, pre-malignant) and MCF10CAIa (CAIa, malignant) [ 24 ]. We showed that, while the cytoskeleton of the malignant CAIa cell line is, as expected, softer than normal A cells, its PM is surprisingly stiffer and correlates with higher surface chol content and cell malignancy [ 23 ].…”
Section: Introductionmentioning
confidence: 82%
“…Here, Young’s moduli of approximately 50–300 kPa in HaCaT were determined ( Heu et al, 2012 ). Another study utilized the Peak Force QNM mode to address the role of cholesterol assemblies on the mechanical behavior of mammalian breast cancer cells (MCF10), and observed Young’s moduli of approximately 5–44 kPa ( Dumitru et al, 2020 ). Calzado-Martin et al studied the effect of actin organization on the stiffness of breast cancer cells lines by Peak Force QNM mode, which revealed Young's moduli of approximately 50–150 kPa ( Calzado-Martín et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the 2000s, numerous studies in various types of cancer strengthened the evidence for the modulation of cell nanomechanical features, such as stiffness, viscoelasticity and deformability, with cell transformation and cancer progression. In breast cancer especially, analysis of the benign MCF10A, premalignant MCF10AT and invasive malignant MCF10CA1A, MDA-MB-231 and MCF7 cell lines showed reduction in stiffness and viscoelasticity: i.e., breast cancer cells were softer and more fluid than their benign counterparts [ 29 , 30 , 31 , 32 , 33 ]. AFM measurements were also conducted in melanoma cell lines representative of different stages of tumor progression, from normal human epidermal melanocytes (NHEM) to metastatic melanoma cells (WM239A), with intermediate non-invasive and locally invasive cell lines (SBC12 and WM115).…”
Section: Stiffness Viscoelasticity and Deformability Of Cultured Cancer Cellsmentioning
confidence: 99%